War and Religion; or, How the First World War Changed Hasidism. - WODZIŃSKI, MARCIN (Jewish Quarterly Review)
An essay is presented on the aftermath of World Wars on Hasidism, Jewish religious sect in Europe. The author offers brief history of political, geographical and demographical challenges faced by Hasidic followers and emergence of new ideologies in Hasidism. Topics discussed include resettlement of Hasidic followers in various countries such as Romania, Poland and Belarus; contraction of followers; and reforms within the religion.